THE WELFARE OF WORKERS IN ANIMAL HOUSING - SAMPAIO, CARLOS A. DE P.; NÄÄS, IRENILZA DE A.; SALGADO, DOUGLAS D. (Revista Brasileira de Engenharia de Biossistemas, 2009)
The objective of this work was to determine the medium time of permanence of the workers during thedevelopment of his functions in his worker’s journey in swine housing confinement. Also, there wasevaluated the thermal comfort environmental of the workers involved in the activities referring to thistype of production. The results showed that the workers remained four hours by day, in the average, inthe same space of production during the daily journey, and dedicating the another half time in otheractivities as transport of feed and internal dislocations. The effective temperature register used toanalyze thermal comfort was Thom (1959) were less of the limits allowed, between 18.9 e 25.6oC andthe Wet Bulb and Temperature of Globe Index (WBTG) was not exceeded by the Brazilian Norms (NR-15) in the most unfavorable period of the working day.